New design of the tractor exhaust muffler based on computational fluid dynamics analysis - Samoilenko, D. E. (НТУ "ХПИ", 2013)
New regulations and standards for noise emission increasingly compel the automotive firms to make some improvements in exhaust systems of engines which include the muffler. First of all such improvement concerns the decreasing of engine noise. Nowadays, the perforated reactive mufflers which have an effective damping capability are specifically used for this purpose. New designs should be analyzed with respect to both acoustics and back pressure. In this study, a new design of reactive perforated mufflers are investigated numerically by using computational fluid dynamics (CFD) tools. Back pressure was obtained based on the flow field analysis and compared for commercial and new design mufflers.

Новые стандарты и нормативы по уровню шума автотракторных двигателей заставляют производителей совершенствовать выпускные системы ДВС. В первую очередь, такие улучшения касаются снижения уровня шума. В приведенном исследовании новая конструкция реактивного глушителя предложена для тракторного дизеля. Выполнены газо- динамические расчеты с использованием программ вычислительной газовой динамики (CFD). Уровень противодавления был установлен по результатам анализа течения газа через глушитель, и выполнено сравнение этого параметра для серийной и новой конструкции глушителей.
Новая конструкция глушителя тракторного дизеля, разработанная по результатам анализа газодинамических расчетов